PERAN GURU DALAM MENANAMKAN AKHLAKUL KARIMAH PADA ANAK USIA DINI DI RA AL-WASHLIYAH BANDAR DURIAN - Juminem, Juminem (STIT Al-Ittihadiyah Labuhanbatu Utara, 2024)
This study aims to describe the role of teachers in instilling good morals in Early Childhood Education children at RA Al-Washliyah Bandar Durian. This research uses qualitative field techniques. The results show that the role of early childhood education teachers in instilling character includes: 1) the teacher as a demonstrator, that is, the teacher teaches how to perform ablution and guides children in performing dhuha prayers; 2) the teacher as a classroom manager, where outside of lessons the teacher organizes books scattered on the floor and during class helps form groups when children play while learning; 3) the teacher as a mediator or facilitator, whereby during the learning process children learn about hijaiyah letters, and the teacher provides images of hijaiyah letters and puppet shows; 4) The teacher as a motivator means the teacher uses rewards for disciplined children by giving star pictures on the board and hands, and then punishing children who are not disciplined by asking them to repent, and to donate every Friday. 5) The teacher as a model means the teacher provides an example of good behavior to children, so that by observing, the children will easily remember it.